Nations at dawn--China, Russia, and America - Stoessinger, John G. (McGraw-Hill, 1994)
Retitled from Nations in Darkness, this classic continues its exploration of the relationship triangle of three superpowers: China, Russia, and the United States. Stoessinger frames the dynamics of these constantly-evolving linkages in terms of how each perceives the others. This edition significantly reworks material on the former Soviet Union. Stoessinger chronicles the undoing of the Soviet Union and relates its ongoing efforts at the establishing of a true democracy while also reexamining China's "Old Guard" and speculating on the emergence of new forces and new directions there